An enigmatic term of ‘bean-counter’: A changing phenomenon in Indonesia’s accountant - Marko S Hermawan; Ayuphita Tiara Silalahi (Jurnal Akuntansi dan Auditing Indonesia, 2022)
The term 'bean-counter' came from the image of an accountant that has a boring, dull, and colorless life. This stereotyping could lead to a negative association with the accounting profession. Nevertheless, only some countries worldwide have the same perception of the accountant image profession. The study attempts to investigate Indonesian accounting graduates in the productive age group towards being an accountant. A qualitative data collection that measures distinct leader, manager and professional roles preference is used, with a semi-structured interview in three diverse perspectives from the accounting students, accounting graduates, and accounting professionals. The findings suggest that there is no perception of an accountant as a bland and colorless life job; rather, they realize that accounting is more than bookkeeping and tracking numbers. Accountants nowadays need to be creative, and the job is quite challenging from this millennial’s point of view.